Effect of Hydroxychloroquine on Clinical Improvement and Mortality Among Patients with COVID-19 Admitted to Four General Hospitals in Saudi Arabia - Alghamdi, Mohammed; Aljuhani, Nasser; AL-Somali, Afrah; Alzahrani, Saeed; Alotaibi, Rashed; Siddiqua, Salma; Naitah, Marwah; albelewi, Sayda; Alghamdi, Ahmed; Alotaibi, Fayez; AlQarni, Abdullmoin; Al-Hariqi, Khalid; et al. (International Journal of Coronaviruses, 2020)
Background The use of hydroxychloroquine in coronavirus disease (COVID-19) pandemic raised significant concerns as regards safety and efficacy in hospitalized patients. The objective was to examine the effect of hydroxychloroquine on clinical improvement and mortality among hospitalized patients with COVID-19. Methods A prospective cohort study was conducted at four general hospitals in the Western region, Saudi Arabia. Patients who had absolute or relative contraindication for using hydroxychloroquine were excluded. Patients concomitantly receiving other medications including azithromycin, antivirals, and supportive treatment were not excluded. Results A total 267 patients were included in the current analysis; 185 (69.3%) on hydroxychloroquine and 82 (30.7%) on non-hydroxychloroquine treatments. The average age was 46.0±13.3 years and 78.3% of the patients were males. Approximately 95.9% of the patients were symptomatic with mild (50.6%), moderate (32.6%), severe (8.2%), or ARDS symptoms (4.5%). Compared with no hydroxychloroquine, those on hydroxychloroquine had significantly longer length of stay (11.5±7.1 versus 7.8±4.3 days, p<0.001), more ICU admission (22.7% versus 9.8%, p=0.012), and more intubation (12.4% versus 3.7%, p=0.026). Improvement of symptoms (84.3% versus 81.7%, p=0.595) and hospitalization death (7.0% versus 1.2%, p=0.071) were not significantly different between groups. With exception of length of stay, the association of hydroxychloroquine with the above negative outcomes disappeared after adjustment for several factors including disease severity and concomitant use of azithromycin. Conclusions Hydroxychloroquine is not associated with better improvement of symptoms compared with other treatments. Moreover, it is associated with longer length of stay but not mortality or ICU admission in adjusted analysis.
Keywords: COVID-19; pandemic; hydroxychloroquine; efficacy; mortality; Saudi Arabia